Physical properties of CeIrSi with trillium-lattice frustrated magnetism - Kneidinger, F.; Zeiringer, I.; Siderenko, A.; Bauer, E.; Michor, H.; Rogl, P.; Sereni, J.G.; Sereni, Julián (American Physical Society, 2019)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina